2018
DOI: 10.1002/jhet.3132
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Bioactivity of Quinoline‐3‐carboxamide Derivatives

Abstract: Twelve novel substituted 2‐chloroquinoline‐3‐carboxamide derivatives were prepared from acetanilides using the Vilsmeier–Haack reaction, producing 2‐chloro‐3‐carbaldehyde quinolines, followed by oxidation of the 3‐carbaldehyde to the carboxylic acid and coupling this group with various anilines. The structures of the synthesized compounds were confirmed by NMR, mass spectrometry, and single crystal X‐ray diffraction. The chemical shifts of H‐5 and H‐8 were shown to be influenced by the substituent at C‐6. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Govender and coworkers introduced carboxamide functional group derivatives at third position of quinoline ring, and the best antimicrobial results was obtained with the compound 64a showing 3.79 mM against methicillin-resistant Staphylococcus aureus (MRSA) strains, and fluorine compound 64b as 1.79 mM against the S. aureus. Moreover, they found that F I G U R E 7 Quinoline derivatives with potential anti-tubercular activity the electron donating moieties at quinoline ring contributes to the antibacterial activity (Govender et al, 2018). Karad et al reported the synthesis of morpholinecontaining quinoline scaffolds with oxadiazole moiety at third position and performed an in-vitro antibacterial activity among which the compound 65 provides a good result against S. pneumonia with 0.146 mM MIC (Karad et al, 2017).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Govender and coworkers introduced carboxamide functional group derivatives at third position of quinoline ring, and the best antimicrobial results was obtained with the compound 64a showing 3.79 mM against methicillin-resistant Staphylococcus aureus (MRSA) strains, and fluorine compound 64b as 1.79 mM against the S. aureus. Moreover, they found that F I G U R E 7 Quinoline derivatives with potential anti-tubercular activity the electron donating moieties at quinoline ring contributes to the antibacterial activity (Govender et al, 2018). Karad et al reported the synthesis of morpholinecontaining quinoline scaffolds with oxadiazole moiety at third position and performed an in-vitro antibacterial activity among which the compound 65 provides a good result against S. pneumonia with 0.146 mM MIC (Karad et al, 2017).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…There are two compounds in the database which have an amide group attached to C3, GICGIL [2-chloro-N-(4-fluorophenyl)-6-methylquinoline-3-carboxamide; Govender et al, 2018] and SUZHEB (N-isopropyl-6-methyl-2-phenylquinoline-3-carboxamide; Benzerka et al, 2010). In both these compounds, the amide group is inclined to the quinoline moiety, unlike in molecule 1.…”
Section: Database Surveymentioning
confidence: 99%
“…Initially, the reaction was attempted with quinoline-2-chloro-3-carbaldehyde (Scheme 1). Quinoline-2-chloro-3-carbaldehyde, 3-oxo-3-phenylpropanenitrile, and phenyl-β-enamine were refluxed in ethanol for 8 h (quinoline-2-chloro-3-carbaldehyde, [4,22] 3-oxo-3phenylpropanenitrile, [23] and β-enamines [24,25] were prepared following the literature reported procedure, refer ESI for detailed synthetic procedure). The reaction progress was monitored by TLC.…”
Section: Synthesis and Characterization Of Quinolinyl-14-dihydropyrimentioning
confidence: 99%